Promoting gender equality, social inclusion and biodiversity conservation in Nepal’s home gardens - Elias, Marlène; Gauchan, D.; Gotor, Elisabetta; Sthapit, B.R. (Bioversity International, 2017)
Bioversity International, the Nepalese LI-BIRD NGO and the Swiss Agency for Development Cooperation led a project from 2002-2012 in Nepal's mid-hills and Terai to promote technologies, approaches and methods for sustainable on-farm management of plant genetic resources and improve food security through the use of home gardens. The Home Gardens project was a successful example of increasing production, consumption and income of the rural poor, and has made an important contribution to strengthening the capacities of farmers and promoting more equitable gender relations.